2017
DOI: 10.1016/j.vaa.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical effects of epidural levobupivacaine morphine versus bupivacaine morphine in dogs undergoing elective pelvic limb surgery

Abstract: Objective To evaluate the efficacy, in terms of the amount of rescue analgesia required, and the clinical usefulness of epidural injection of morphine with bupivacaine or levobupivacaine for elective pelvic limb surgery in dogs during a 24-hour perioperative period.Study design Prospective, blinded, randomized clinical study.Animals A group of 26 dogs weighing 31.7 ± 14.2 (mean ± standard deviation) kg and aged 54 ± 36 months.Methods All dogs were premedicated with methadone intravenously (0.2 mg kg e1 ) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…The cranial part of both ovaries and cervix uteri were ligatured. Local anaesthetics, 0.5% BP (Marcaine ® ) 6 [4.4 mg/ kg] and 0.5% LP (Chirocaine ® ) 4 [4.4 mg/kg], were prepared using the equal volume of saline following calculation of the individual doses. The preparations were then sprayed over the ovaries, uterine broad ligaments and cervix uteri.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The cranial part of both ovaries and cervix uteri were ligatured. Local anaesthetics, 0.5% BP (Marcaine ® ) 6 [4.4 mg/ kg] and 0.5% LP (Chirocaine ® ) 4 [4.4 mg/kg], were prepared using the equal volume of saline following calculation of the individual doses. The preparations were then sprayed over the ovaries, uterine broad ligaments and cervix uteri.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Inexpensive, easily available and applicable local anaesthetics have been widely used epidurally, intraarticularly, perineurally or intraperitoneally in veterinary and human medicine to prevent or relieve pain [1,6,17,18,28]. Bupivacaine (BP) is a long-acting amino amide local anaesthetic agent [5,20].…”
Section: Introductionmentioning
confidence: 99%
“…Complications of epidural administration include spinal injection, pruritus or urine retention (Otero & Campoy, 2013;Cerasoli et al 2017). Although none of these complications occurred in the present study, a slower recovery was observed in the EpiG with 31.6% of dogs still showing signs of sedation at 2 hours.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 45%
“…Epidural anaesthesia allows postoperative pain management with the use of different drugs, such as opioids, local anaesthetics or α2--adrenoceptor agonists (DeRossi et al 2016;Steagall et al 2017;Garcia-Pereira, 2018). Although it is a commonly used technique, complications such as hypotension, bradycardia, ventilatory depression or urinary retention have been reported (Jones, 2001;Cerasoli et al 2017). Moreover, epidural anaesthesia produces temporary motor block (Adami et al 2012).…”
Section: Introduction ( Word Count 4127)mentioning
confidence: 99%
“…Em conjunto a isso, observou-se que o animal teve uma recuperação tranquila, com ausência de vocalização e expressão álgica, o que permite presumir que o bloqueio anestésico foi eficiente. Comparando-se a outras espécies como cães, por exemplo, para procedimentos de osteossíntese de membros pélvicos, bloqueios regionais, como peridurais, utilizando associação de duas ou mais classes farmacológicas, muitas vezes se fazem necessários para obtenção de analgesia trans e pós-operatória eficaz, conforme descrito por Cerasoli et al (2017), apesar de os animais sob efeito de anestesia geral inalatória muitas vezes necessitarem de resgate analgésico transcirúrgico com opioides (Arnholz et al, 2017).…”
Section: Discussionunclassified